Naming Human Anatomy and Diseases in Maanyan Language - Septiana, Dwiani; Yulianti, Andi Indah (Indonesian Journal of EFL and Linguistics, 2022)
The purposes of this research are to describe and document the lexicons related to human anatomy and diseases in the Maanyan language as well as explain their structures and meaning. This research used the theory of ethnolinguistics which focuses on the documentation, description, and classification of indigenous languages by viewing the language as a lexicon and grammar. It deployed an ethnographic research method. It was conducted in the Maanyan community in East Barito Regency, Central Kalimantan. The data were lexicons related to the names of diseases, human anatomy and human body conditions in the Maanyan language. They were analysed by classifying lexicons, explaining their meaning, and describing them based on the word structure. The results indicate that in the Maanyan language there are 179 lexicons associated with the human anatomy and the names of diseases. They are 92 lexicons related to human anatomy, 46 lexicons about the human body’s conditions, and 41 lexicons of disease names. According to the word structure, these lexicons consist of single, derived, and compound forms.